Efficacy of insecticide impregnated bed-nets to control malaria in a rural forested area in Southern Cameron - G. le Goff (Memórias do Instituto Oswaldo Cruz., 1992)
Due to current spreading of chemoresistant strains of Plasmodium falciparum malaria control must incorporate vector control programmes. Due to well known constraints house sprayings cannot be performed as before. Personal protection can be developed and a large scale use of insecticide treated bed-nets appeared to be very useful to reduce man-vector contact in Asia, South America and West and East Africa. No trial has done is forest Central Africa where transmission is permanent. We performed such a trial in the southern part of Cameroon (using deltamethrin, at 25mg/m*) and obtained similar data to those observed in the Gambia Burkina Faso and Tanzania with a noteworthy reduction of both transmission and high parasitaemia of P. falciparum (respectively 78% and 75%) meaning a drop of malaria morbidity.